Optimalisasi Kinerja Solar Shading Sebagai Usaha Menurunkan Solar Gain pada Bangunan - Dewi, Cynthia Permata; Utomo, Joko Budi; Choirotin, Ismi (RUAS, 2018)
A glassÂ facade is commonly used by modern building nowadays, even in the tropical area with its characteristic. Thus, buildings often face a problem with thermal comfort. Passive design strategy supposed to be considered by the architect in order to avoid inconvenience with the heat. This strategy utilized the architectural element as the tools to reach the comfort level. The aim of this study was to optimize the thermal behavior of the building itself by the modification of solar shading types and materials. EnergyPlus was used as a simulation tool in this study. The results show that solar gain exterior window can be reduced by 52,73% by using concrete louvre and wood louvre.